Genome‐wide association study of chronic periodontitis in a general German population. (11th September 2013) - Teumer, Alexander; Holtfreter, Birte; Völker, Uwe; Petersmann, Astrid; Nauck, Matthias; Biffar, Reiner; Völzke, Henry; Kroemer, Heyo K.; Meisel, Peter; Homuth, Georg; Kocher, Thomas
Abstract Aim To identify loci associated with chronic periodontitis through a genome‐wide association study (GWAS). Materials and Methods A GWAS was performed in 4032 individuals of two independent cross‐sectional studies of West Pomerania (SHIP n = 3365 and SHIP‐TREND n = 667) with different periodontal case definitions. Samples were genotyped with the Affymetrix Genome‐Wide Human SNP Array 6.0 or the Illumina Human Omni 2.5 array. Imputation of the HapMap as well as the 1000 Genome‐based autosomal and X‐chromosomal genotypes and short insertions and deletions (INDELs) was performed in both cohorts. Finally, more than 17 million SNPs and short INDELs were analysed. Results No genome‐wide significant associations were found for any periodontitis case definition, regardless of whether individuals aged >60 years where excluded or not. Despite no single SNP association reached genome‐wide significance, the proportion of variance explained by additive effects of all common SNPs was around 23% for mean proximal attachment loss. Excluding subjects aged >60 years increased the explained variance to 34%. Conclusions No single SNPs were found to be genome‐wide significantly associated with chronic periodontitis in this study.